Examining gender specific treatment programs in women's prisons - Gibson, Jenny (British educational research journal, 2016)
The female offender population has been the fastest growing segment of the correctional population. Historically, victimization and trauma are highly correlated with substance abuse and dependency that are known to have a significant impact on females' pathway toward criminal lifestyle, incarceration, relapse, and recidivism. Due to feminists' research, today we know that females offenders' pathways toward substance abuse, criminal behavior, and recidivism differ from those of males. As a result, a discussion about the development and implementation of gender-specific substance abuse treatment programs has been initiated. The purpose of this study is to discover if research recommendations proposed, have been taken to consideration and implemented. The qualitative data was derived from various sources. The results suggest that several correctional institutions aim to provide treatment that addresses female offenders' gender-specific needs